2015
DOI: 10.1002/bjs.9809
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation therapy for rectal cancer in the distal rectum followed by organ-sparing transanal endoscopic microsurgery (CARTS study)

Abstract: TEM after chemoradiotherapy enabled organ preservation in one-half of the patients with rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 47 publications
5
113
1
7
Order By: Relevance
“…Local excision of advanced rectal cancers with curative intent remains a debatable issue. The review recommended that TEM only be used for palliative cases in T2-T3 tumors, nevertheless, researchers in several studies have described that TEM is safe and effective for patients with rectal carcinoma pT2 N0 low risk after neoadjuvant therapy and pT3 N0 low risk and complete response after neoadjuvant therapy who refused abdominal surgery [4,5,[9][10][11][12][13]22,26,[30][31][32]. Our experience has shown that neoadjuvant therapy followed by TEM to treat T2-3 N0 rectal cancer is well tolerated and effective.…”
Section: Discussionmentioning
confidence: 90%
“…Local excision of advanced rectal cancers with curative intent remains a debatable issue. The review recommended that TEM only be used for palliative cases in T2-T3 tumors, nevertheless, researchers in several studies have described that TEM is safe and effective for patients with rectal carcinoma pT2 N0 low risk after neoadjuvant therapy and pT3 N0 low risk and complete response after neoadjuvant therapy who refused abdominal surgery [4,5,[9][10][11][12][13]22,26,[30][31][32]. Our experience has shown that neoadjuvant therapy followed by TEM to treat T2-3 N0 rectal cancer is well tolerated and effective.…”
Section: Discussionmentioning
confidence: 90%
“…Если прини-мать во внимание тот факт, что вероятность полного клини ческого ответа при «раннем» раке существенно выше, чем при стадиях Т3-4, применение подобного подхода может быть обосновано у данных пациентов на этапе первичной диагностики. Подтверждением тому являются данные исследований CARTS [23], ACOSOG Z6041 [24], в которые включали пациентов с раком прямой кишки стадий Т1-Т3а-bN0 в пре делах 10 см от ануса. Пациентам проводили пролонгирован-ную ХЛТ с оценкой эффекта лечения через 8-12 нед и локальным иссечением с применением трансанальной эндомикрохирургии остаточной опухоли у пациентов с хорошим клиническим ответом.…”
Section: Discussionunclassified
“…Необходимость до-полнительного лечения определяли по результату пато-морфологического заключения. По результатам иссле-дований CARTS, ACOSOG Z6041 органосохраняющее лечение удалось выполнить у 55 и 66 % больных соот-ветственно [23,24].…”
Section: Discussionunclassified
“…It has been demonstrated that low-risk T1 rectal cancer have a very low rate of lymphnode metastasis which allow to consider TEM a safe procedure [19] [23]- [26]. The indications for TEM have considerably expanded since its introduction, in parallel with technical advances and surgeon experience, but patient accurate preoperative selection is the key element to the successful performance of TEM.…”
Section: Discussionmentioning
confidence: 99%